DOES EVIDENCE BASED MEDICINE SUPPORT THE EFFECTIVENESS OF SURGICAL FACEMASKS IN PREVENTING POSTOPERATIVE WOUND INFECTIONS IN ELECTIVE SURGERY? - Bahli, Zahid Mehmood (Journal of Ayub Medical College Abbottabad, 2009)
Background: The incidence of postoperative wound infection is usually not the cause of death but it increases the length of hospital stay and cost of care and morbidity. Since their introduction a century ago there is still controversy about primary purpose of the facemasks as whether they provide protection for the patient from surgical team or weather they protect surgical team from the patient? The Objectives of this study were to critically analyze and systematically review the randomized trials regarding effectiveness of surgical facemasks in preventing post operative wound infection in elective surgery. Method: Systematic literature review and analysis of all available trials (randomized controlled trials) regarding use of surgical face masks in elective surgeries. Medline (1966-2007), Embase (1996-2007), Cochrane database, Pubmed, Google Scholar, were searched for the selection of literature for the review. Results: No significance difference in the incidence of postoperative wound infection was observed between masks group and groups operated with no masks (1.34, 95% CI, 0.58-3.07). There was no increase in infection rate in 1980 when masks were discarded. In fact there was significant decrease in infection rate (p<0.05). Conclusion: From the limited randomized trials it is still not clear that whether wearing surgical face masks harms or benefit the patients undergoing elective surgery. Keywords: Surgical face mask, postoperative wound infection, surgical site infection, face masks, prevention of postoperative wound infection, effectiveness of surgical face mask